2018
DOI: 10.1007/s10616-018-0234-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derived endothelial progenitor cells retain their phenotype and functions after a limited number of culture passages and cryopreservation

Abstract: A critical limitation for tissue engineering and autologous therapeutic applications of bone marrow derived EPCs is their low frequency, which is even lower in number and activity level in patients with cardiovascular risk factors and other diseases. New strategies for obtaining and reserving sufficient ready-to-use EPCs for clinical use have hit major obstacles, because effects of serial passage and cryopreservation on EPC phenotype and functions are still needed to be explored. The present study aims at inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The morphology of rabbit EPCs and BEPCs cultured for less than 2-3 weeks were stable during the culture with spindle-shaped appearance (Figure 1) that agreed with the previous studies [41,42,44]. The same shape of the early EPCs morphology originated from peripheral blood and/or bone marrow was observed for human [54], mouse [30], rat [31][32][33]35], goat [38] or chicken [39]. However, it has been demonstrated that longer culture (more than 3 weeks) of rabbit EPCs caused a change of morphology to cobblestone-like cells, although not in BEPCs culture [42,43].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The morphology of rabbit EPCs and BEPCs cultured for less than 2-3 weeks were stable during the culture with spindle-shaped appearance (Figure 1) that agreed with the previous studies [41,42,44]. The same shape of the early EPCs morphology originated from peripheral blood and/or bone marrow was observed for human [54], mouse [30], rat [31][32][33]35], goat [38] or chicken [39]. However, it has been demonstrated that longer culture (more than 3 weeks) of rabbit EPCs caused a change of morphology to cobblestone-like cells, although not in BEPCs culture [42,43].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the doubling time of human umbilical cord-derived EPCs was calculated to be about 40 h [ 55 ]. The population doubling times of rat bone marrow-derived EPCs starting at 104 h (P0) decreased with the subsequent passages to 54 h (P4) and up to 40 h at passages 11 and 12 [ 35 ]. Thus, it seems that the proliferation rate of cultured EPCs may increase in the later passages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations